Using Flat-Panel Perfusion Imaging to Measure Cerebral Hemodynamics: A Pilot Feasibility Study in Patients With Carotid Stenosis. Issue 20 (May 2016) - Lin, Chung-Jung; Guo, Wan-Yuo; Chang, Feng-Chi; Hung, Sheng-Che; Chen, Ko-Kung; Yu, Deuerling-Zheng; Wu, Chun-Hsien Frank; Liou, Jy-Kang Adrian
Abstract : Abstract: Flat-detector CT perfusion (FD-CTP) imaging has demonstrated efficacy in qualitatively accessing the penumbra in acute stroke equivalent to that of magnetic resonance perfusion (MRP). The aim of our study was to evaluate the feasibility of quantifying oligemia in the brain in patients with carotid stenosis. Ten patients with unilateral carotid stenosis of >70% were included. All MRPs and FD-CTPs were performed before stenting. Region-of-interests (ROIs) including middle cerebral artery territory at basal ganglia level on both stenotic and contralateral sides were used for quantitative analysis. Relative time to peak (rTTP) was defined as TTP of the stenotic side divided by TTP of the contralateral side, and so as relative cerebral blood volume (rCBV), relative mean transit time (rMTT), and relative cerebral blood flow (rCBF). Absolute and relative TTP, CBV, MTT, CBF between two modalities were compared. For absolute quantitative analysis, the correlation of TTP was highest ( r = 0.56), followed by CBV ( r = 0.47), MTT ( r = 0.47), and CBF ( r = 0.43); for relative quantitative analysis, rCBF was the highest ( r = 0.79), followed by rTTP ( r = 0.75) and rCBV ( r = 0.50). We confirmed that relative quantitative assessment of FD-CTP is feasible in chronic ischemic disease. Absolute quantitative measurements between MRP and FD-CTP only expressed moderate correlations. Optimization of acquisitions and algorithms is warranted to achieve better quantification.